2008
DOI: 10.1088/0741-3335/50/8/085014
|View full text |Cite
|
Sign up to set email alerts
|

Hamiltonian formulation and analysis of a collisionless fluid reconnection model

Abstract: The Hamiltonian formulation of a plasma four-field fluid model that describes collisionless reconnection is presented. The formulation is noncanonical with a corresponding Lie-Poisson bracket. The bracket is used to obtain new independent families of invariants, so-called Casimir invariants, three of which are directly related to Lagrangian invariants of the system. The Casimirs are used to obtain a variational principle for equilibrium equations that generalize the Grad-Shafranov equation to include flow. Dip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 69 publications
(214 reference statements)
2
88
0
Order By: Relevance
“…We describe the response of the plasma in the resonant layer by using the "fourfield" model of Hazeltine et al [68,69] We note that the the four-field model uses a finite Larmor radius (FLR) expansion for the ion dynamics (kρ i 1, where ρ i is the ion Larmor radius). In the low-collisionality regime of the DIII-D experiments, however, the resonant layers are narrower than the Larmor radius.…”
Section: Formulationmentioning
confidence: 99%
“…We describe the response of the plasma in the resonant layer by using the "fourfield" model of Hazeltine et al [68,69] We note that the the four-field model uses a finite Larmor radius (FLR) expansion for the ion dynamics (kρ i 1, where ρ i is the ion Larmor radius). In the low-collisionality regime of the DIII-D experiments, however, the resonant layers are narrower than the Larmor radius.…”
Section: Formulationmentioning
confidence: 99%
“…To facilitate comparison to earlier models including the cold-ion version of the four-field model [31] and the incompressible (3-field) gyrofluid model, [25] we rewrite the dynamical equations as…”
Section: Formulationmentioning
confidence: 99%
“…Grasso et al [33] have shown that the mixing of such Lagrangian quantities by the convecting flows is an important ingredient in rapid collisionless reconnection. In this respect, it is worth noticing that a limit of this model [31], obtained by neglecting the ion gyroradius, possesses a Poisson bracket of a different type (the sum of direct and semidirect products), leading to only three Lagrangian invariants, two of which undergoing phase mixing.…”
Section: Normal Fields and Jacobimentioning
confidence: 99%
“…One of the early examples is reduced MHD [6], but many models for many purposes have been obtained over the years, e.g. [7,8,9,10,11,12,13,14,15,16]. Sometimes models like these arise from systematic asymptotic expansion, while in other cases they have been proposed in a more ad hoc manner.…”
Section: Introductionmentioning
confidence: 99%